Intracerebral Nontraumatic Hemorrhagic Stroke in Children: Case Series and Literature Review. Issue 3 (31st January 2020) - Buonsenso, Danilo; Pata, Davide; Plosnić, Mihael; Musolino, Anna M.; Ferrrara, Pietro; Gambacorta, Alessandro; Piastra, Marco; Chiaretti, Antonio
Abstract : Pediatric stroke is an event caused by disturbance of cerebral circulation that occurs in individuals between 28 days and 18 years of age. Although an uncommon event, pediatric stroke still carries significant morbidity and mortality. Unlike adults, causes of pediatric stroke are various and include vascular, infectious, hematologic, neoplastic, and toxic etiologies. Clinical presentation of nontraumatic intracerebral hemorrhages in older children is similar to adults, however in neonates and infants signs and symptoms can be more subtle, especially with smaller hemorrhages. Management of nontraumatic intracerebral hemorrhage consists of stabilizing the patient, management of the hemorrhage itself, and reduction of the rebleeding risk. Even so, when child reaches a medical care, morbidity and mortality rates are still high. We described a case series of pediatric patients with intracerebral nontraumatic hemorrhagic stroke from different etiologies. Although increasingly recognized, such situations are still poorly described in children and our report offers a good overview on this topic.